Kepemimpinan Situasional Dalam Rangka Meningkatkan Efektivitas Kerja Pegawai Kantor Dinas Pendidikan dan Olahraga (Dikpora) Pekanbaru - Indriyanto, Indriyanto (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
This research can be claasified into descriptive research which consist of one independentvariable namely situational leadership and one dependent variable namely employees workeffectiveness. The research resulted in several conclusions are; (1) The variable of EmployeesWork Effectiveness is shown, 6.19% employees have extremely low work effectiveness, 52.58%employees have low work effectiveness, 34.02% employees have high work effectiveness, and7.22% employees have exteremely high work effectiveness. Based on the research finding, theemployees work effectiveness at Education and Sport Official Government, Pekanbaru can beclassified into low level; (2) The variable of Situational Leadership is shown 6.19% leaders have extremely low of situational leadership, 47.42% leaders have low of situational leadership,41.24% leaders have high of situational leadership, and 5.15% leaders have extremely high of situational leadership. Based on the research finding, the situational leadership at Education and Sport Official Government, Pekanbaru can be classified into low level.